Evaluation of Development Projects on Special Allocation Funds Sources for the Pariaman City Self-Help Housing Program - Rhama Budi Setia; Taufika Ophiyandri; Akhmad Suraji (CIVED, 2025)
This study evaluates the success rate of the program (target accuracy, satisfaction, and community self-reliance) of the special allocation fund (DAK) self-help housing assistance in Pariaman City, a coastal area with a majority of low-income residents and many uninhabitable houses. This program is part of the government's efforts to overcome poverty and deal with slum areas, as stipulated in the Minister of PUPR Regulation No. 7 of 2022. Previous studies may have only focused on one or two dimensions. This study uses a mixed method of quantitative and qualitative. Quantitative data were collected through a questionnaire with a Likert scale to measure target accuracy, satisfaction, and community self-reliance. Qualitative data were collected through in-depth interviews with beneficiaries and related parties to understand their context and experiences related to the program. Data were analyzed quantitatively using descriptive statistics and qualitatively using thematic analysis. The results showed that the program was right on target (more than 80% of respondents gave the highest score), the level of satisfaction was high (more than 70% of respondents gave a score of 4 or 5), and community participation was very good (84.29% of beneficiaries were involved in house construction on average). These findings provide strong empirical evidence of the success of the DAK self-help housing assistance program in Pariaman City. The local government can use the results of this study to strengthen the DAK self-help housing assistance program, for example by increasing budget allocation or expanding the reach of the program.